2017
DOI: 10.2527/jas.2016.0433
|View full text |Cite
|
Sign up to set email alerts
|

Satiety splits drinking behavior into bouts: Organization of drinking in turkeys1

Abstract: The regulation of the drinking behavior of animals is usually overlooked, and the traits associated with it are not well defined. We used a unique data set of measurements of individual drinking behavior in turkeys 1) to validate the system of data generation, 2) to develop a methodology to allow clustering of drinking events and splitting behavior into bouts, and 3) to develop traits related to drinking behavior and its regulation and investigate how these traits may be affected by bird genotype. Visits to dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 26 publications
(3 reference statements)
1
10
0
Order By: Relevance
“…In addition, both lines were selected for leg health and fitness traits. In a previous study, we used these lines to develop a methodology for estimating drinking bout criteria in turkeys [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, both lines were selected for leg health and fitness traits. In a previous study, we used these lines to develop a methodology for estimating drinking bout criteria in turkeys [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the start of the experiment, each bird was fitted with a passive radio-frequency identification (RFID) transponder on the leg, which recorded bird presence inside the drinker. Previous observations suggested that transponders did not affect the birds’ behaviour in any way [ 8 ]. Access to each drinker was regulated by a set of transparent plastic side partitions, which were adjusted to the birds’ size as they grew.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations